Sosialisasi Pemahaman Pariwisata dan Sikap Dasar Hospitaliti dalam Membangun Kawasan Pariwisata Perdesaan Di Kecamatan Tegallalang, Gianyar-Bali - Ni Kade Juli Rastitiati; I Ketut Surata; Made Artajaya (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
One of the duties and responsibilities of Higher Education in Indonesia  is conducting communinity service. Referring to the responsibility, the Study Program of Hospitality Business held a community service in the Vilage of Kenderan, Tegallalang District, Gianyar Regency.  The form of the service was socialization on Tourism Understanding and Basic Hospitality Attitudes in order to build Rural Tourism Destination. The community service was done in Kayangan Villa, Kenderan Village Gianyar on 28-29 October 2021. The objectives of the program was to build the tourism awareness and hospitality attitude  of the society which were required in developing the rural tourism in Tegallalang District which included three villages, namely:  Tegallalang, Taro and Kenderan (Tricovillage). By having the awareness and attitude, it is hoped that the society will be actively take a part in the rural tourism development.